A comparison of global marine surface‐specific humidity datasets from in situ observations and atmospheric reanalysis. (8th April 2013) - Kent, Elizabeth C.; Berry, David I.; Prytherch, John; Roberts, J. Brent
ABSTRACT The accurate estimation of near‐surface marine‐specific humidity is necessary for climate and air–sea interaction applications. Available estimates of monthly mean‐specific humidity spanning the past 50‐years are based on a variety of sources including in situ observations, atmospheric reanalyses and datasets that blend many different data sources. Eight specific humidity datasets are compared and little consensus emerges as to mean values, regional variations and changes over time. For large area averages the datasets do show consistency in their interannual variations and, in the Extratropics, in their seasonal cycles. Adjustments applied to in situ observations from ships are shown to be smaller than differences among the datasets and in well‐sampled regions and periods the in situ data are able to highlight biases in the reanalysis‐based specific humidity estimates. Near surface‐specific humidity estimates from two recent atmospheric reanalysis projects show markedly different responses in Tropical‐specific humidity to the assimilation of satellite radiance measurements that became available in 1999. There is less confidence in reanalysis‐based estimates of specific humidity over the ocean than over land. However the in situ‐based humidity analyses have suffered in recent years with a reduction in observation numbers and lack of information on observation methods and heights. Consequently near‐surface‐specific humidity remains relatively poorly known over the oceans.